A Challenging Case of Patent Ductus Arteriosus Device Closure in an Adult with Unconventional Views and Catheters - Garg, Naveen (Heart Views, 2018)
Abnormally oriented patent ductus arteriosus is expected in adults, which can lead to difficulties while attempting a device closure. Alternate angiographic views like the “right anterior oblique view,” “retrograde approach” and in rare cases, as elicited in the following case scenario, special catheters like the “Tiger(®) catheter” can aid in crossing the lesion and completion of the procedure successfully.